High expressions of BCL6 and Lewis y antigen are correlated with high tumor burden and poor prognosis in epithelial ovarian cancer - Liancheng Zhu; Huilin Feng; Shan Jin; Mingzi Tan; Song Gao; Huiyu Zhuang; Zhenhua Hu; Huimin Wang; Zuofei Song; Bei Lin (Tumor Biology)
Aberrant regulation of BCL6 plays crucial oncogenic roles in various malignant tumors; howbeit, the function of BCL6 in tumorigenesis of ovarian cancer remains unclear. The aim of this study is to investigate the role of BCL6 in ovarian cancer. The methods of immunohistochemical staining, quantitative real-time polymerase chain reaction, immunocytochemical staining, and gene expression profile enrichment analysis were performed to identify the possible role of BCL6 in ovarian cancer. We observed that the expression of BCL6 was significantly higher in ovarian cancer tissues and correlated with higher tumor burden including advanced International Federation of Gynecology and Obstetrics stages, poor differentiation, Type II ovarian cancer, the presence of >1 cm residual tumor size, and appearance of recurrence or death (all p  < 0.05). The expression patterns of Lewis y were similar to these of BCL6. Multivariate Cox analysis demonstrated that advanced International Federation of Gynecology and Obstetrics stage, lymph node metastasis, residual tumor size >1 cm, as well as high expressions of BCL6 and Lewis y antigen were independent factors of worse progression-free survival and overall survival (all p  < 0.05). There was a positive correlation of the expressions of BCL6 and Lewis y antigen. The associated genes with BCL6 in response to Lewis y antigen were identified, including four upregulated genes ( SOCS3, STAT1, PPARG , and GADD45A ) and three downregulated genes ( ACAN, E2F3 , and ZBTB7B ). In conclusion, the high expressions of BCL6 and Lewis y antigen are associated with development, high tumor burden, and worse prognosis of ovarian cancer and targeting BCL6 could be a novel therapeutic strategy for ovarian cancer treatment.